2021
DOI: 10.1111/liv.15049
|View full text |Cite
|
Sign up to set email alerts
|

The protease‐inhibitor SerpinB3 as a critical modulator of the stem‐like subset in human cholangiocarcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(31 citation statements)
references
References 47 publications
3
28
0
Order By: Relevance
“…There are several hypothesized mechanisms by which SerpinB3 could affect cancer-relevant phenotypes (e.g., impact on the stem cell state, resistance to apoptosis, invasion). A recent study in cholangiocarcinoma found that SerpinB3 was expressed in a stem-like subset of cells and that knockdown of SerpinB3 resulted in decreased invasion and proliferation (Correnti et al, 2021). In addition to its roles in cancer, SerpinB3 is Cell Reports 40, 111348, September 13, 2022 7 Article ll expressed in hepatic stem cells, where SerpinB3 expression correlates with decreased activated caspase 3 (Villano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…There are several hypothesized mechanisms by which SerpinB3 could affect cancer-relevant phenotypes (e.g., impact on the stem cell state, resistance to apoptosis, invasion). A recent study in cholangiocarcinoma found that SerpinB3 was expressed in a stem-like subset of cells and that knockdown of SerpinB3 resulted in decreased invasion and proliferation (Correnti et al, 2021). In addition to its roles in cancer, SerpinB3 is Cell Reports 40, 111348, September 13, 2022 7 Article ll expressed in hepatic stem cells, where SerpinB3 expression correlates with decreased activated caspase 3 (Villano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The copyright holder for this preprint (which this version posted April 1, 2023. ; https://doi.org/10.1101/2023.03.29.534766 doi: bioRxiv preprint including hepatocellular carcinoma (34), cholangiocarcinoma (32), PDAC (36), glioblastoma (33), and breast cancer (35,45). In cancer, SERPINB3 has various functions including inhibition of radiation/anti-cancer drug-induced apoptosis, protein degradation, and intratumor infiltration of natural killer cells (27,34,46), and to promote metabolic reprogramming, angiogenesis, epithelial-mesenchymal transition, and secretion of inflammatory mediators (28,(32)(33)(34)(35)(36). SERPINB3 also upregulates MYC (30,31), which leads to the maintenance of cancer stemness (32,33).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, SERPINB3 was ranked one of the top and robustly upregulated genes in the basal-like/progenitor subtype (Supplementary Table 2). SERPINB3 is also known as squamous cell carcinoma antigen (24)(25)(26)(27), associates with hypoxia (28,29), and promotes MYC activation (30,31), cancer stemness (32,33), metabolic reprogramming (28), and inflammation (34)(35)(36). These functions overlap the characteristics of basal-like/squamous subtype (3), and we chose SERPINB3 for further investigation.…”
Section: Serpinb3 Is Upregulated In Basal-like/squamous Subtype Of Pd...mentioning
confidence: 99%
“…There are several hypothesized mechanisms by which SerpinB3 could affect cancer-relevant phenotypes (impact on the stem cell state, resistance to apoptosis, invasion). A recent study in cholangiocarcinoma found that SerpinB3 was expressed in a stem-like subset of cells and that knockdown of SerpinB3 resulted in decreased invasion and proliferation (Correnti et al, 2021). In addition to its roles in cancer, SerpinB3 is expressed in hepatic stem cells, where SerpinB3 expression correlates with decreased activated caspase 3 (Villano et al, 2014).…”
Section: Discussionmentioning
confidence: 99%